High-temperature stable and high-output cellulose-based triboelectric material as well as preparation method and application thereof

By sulfonating the nanocellulose material and preparing it into a film, and coating it with a silane hydrolysate, it forms a stable and high-output cellulose-based friction electrical material at high temperatures, solving the problem of reduced charge storage capacity of friction electrical material in high temperature environments, and achieving efficient high-temperature stability and output performance.

CN119684658AInactive Publication Date: 2025-03-25JIANGNAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411902399.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The charge storage capacity of triboelectric materials in high-temperature environments is reduced, resulting in the limitation of the development of high-output TENGs under high-temperature conditions.

Method used

After mixing the nanocellulose material with water, isopropanol and sodium vinyl sulfonate and undergoing sulfonation reaction, a film is prepared and coated with a silane hydrolysate to form a stable high-output cellulose-based friction electrical material at high temperature.

Benefits of technology

It achieves high output performance and structural stability under high temperature environments, reduces the charge dissipation rate by 83%, and maintains a charge density of 95% under 250°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684658A_ABST
    Figure CN119684658A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano energy, and particularly relates to a stable and high-output cellulose-based triboelectric material at high temperature and a preparation method and application thereof. The preparation method comprises the following steps: sulfonating nano cellulose, spin-coating to form a film, spin-coating silane hydrolysate on the surface, and drying to form the film. The surface deep trap density of the modified cellulose is improved by one order of magnitude, so that the charge storage capacity of a dielectric is improved, and the charge dissipation rate is reduced by 82%. In addition, the interaction of multiple non-covalent bonds improves the mechanical properties at high temperature. Therefore, the synergistic strategy realizes that the cellulose-based triboelectric material keeps bonding strength and ultrahigh surface charge density (152 [mu] C / m < 2 > at 250 DEG C) in a high-temperature environment. The invention provides a new method for developing a stable and high-output self-powered biomass-based wearable sensor in an extreme environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nano energy technology, and specifically relates to a cellulose-based triboelectric material with stable high output at high temperature, and a preparation method and application thereof. Background Art

[0002] Since the Industrial Revolution, the rapid development of science and technology has accelerated people's pace of exploring the unknown world. In order to protect and monitor people's health when exploring various extreme environments, the development of energy devices with highly integrated human-computer interaction functions has been promoted, among which stable matching power supplies are an important component of flexible electronic devices. In this context, triboelectric nanogenerators (TENGs) based on contact charging and electrostatic inductive coupling effects have emerged. Due to their low cost, high efficiency, environmental protection and diverse material selection, they have broad application prospects in energy harvesting and self-powered sensors in extreme environments.

[0003] In order to obtain higher surface charge density for efficient energy harvesting, a lot of work has been done, including material selection, structural optimization, and external pumping of charges. However, high temperature can lead to structural degradation of the friction layer and rapid dissipation of interfacial charges, thereby reducing its ability to store charge, resulting in great limitations on the development of high-output TENGs in high-temperature environments. However, this design usually causes the material to become more active at high temperatures, and the entropic advantage causes the polymer chains to dissociate rapidly, reducing the thermal stability of the material. If triboelectric materials have both high enthalpy gain and high unbound states, they can maintain high structural stability even in high-temperature environments.

[0004] The method of enhancing the dielectric constant is often used to alleviate the charge dissipation phenomenon, which is often accompanied by enhanced dielectric loss during this period, which is caused by the enhanced interaction between the electric field and the charge. Therefore, the generated electrical energy cannot be stored or transferred, but is converted into heat energy, which reduces the effective energy conversion efficiency and electrical signals. Therefore, it is challenging to find new technologies to improve the charge storage capacity of the friction layer under high temperature environment. Increasing the deep well density on the surface of the material can effectively enhance its charge capture ability. Although the semiconductor industry has conducted extensive research on the carrier capture mechanism, there are few reports on the impact of deep wells on the output performance of TENG. However, deep wells with high density distributed on the surface of triboelectric materials can effectively store charges and slow down the electron pyroelectric phenomenon, thereby maintaining stable output under high temperature environment. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a cellulose-based triboelectric material with stable high output at high temperature, which has the advantages of easy availability of raw materials, simple process, superior performance, etc.

[0006] The technical problems to be solved are achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a cellulose-based triboelectric material with stable high output at high temperature, comprising the following steps:

[0008] S11: mixing a nanocellulose material, water, isopropanol and sodium vinyl sulfonate (SV), adding alkali for sulfonation at 40-95° C. for 5-40 hours to obtain a sulfonated cellulose material; the nanocellulose material is selected from cellulose nanofibers, quaternized cellulose nanofibers, carboxylated cellulose nanofibers or bacterial cellulose;

[0009] S12: preparing the sulfonated cellulose material into a membrane to obtain a sulfonated cellulose membrane (SCNF);

[0010] S13: coating the surface of the sulfonated cellulose membrane with silane hydrolyzate and then drying to obtain the high-temperature stable high-output cellulose-based triboelectric material (SCNF-NH2); the silane hydrolyzate is obtained by mixing polar silane with symmetrical electrostatic potential distribution in ethanol aqueous solution at 40-80°C for 6-18h; the coating method is selected from spin coating, spot coating or coating.

[0011] Preferably, in step S11, the diameter of the nanocellulose material is 3-20 nm and the length is 1-20 μm.

[0012] Preferably, in step S11, the mixing method is ultrasonic dispersion for 0.5-4h.

[0013] Preferably, in step S11, the mass ratio of sodium vinyl sulfonate to nanocellulose material is 8-72:100, and the mass ratio of alkali to sodium vinyl sulfonate is 6-16:100.

[0014] Preferably, in step S11, the base is selected from sodium hydroxide, and the mixture is stirred for 1-3 hours after the base is added.

[0015] Further, the cellulose sulfonation reaction treatment is as follows: sodium vinyl sulfonate (SV) is added to a mixed solution of 0.5-2.3 g of nanocellulose, 1-5 mL of ultrapure water and 75-140 mL of isopropanol, with the ratio of SV to cellulose being 8-72%, and ultrasonic dispersion is performed for 0.5-4 hours. Then, NaOH is added to the above solution, with the weight ratio of NaOH to SV being 6-16%, and stirred for 2 hours, and then heated to 40-95° C. and stirred for 5-40 hours.

[0016] Preferably, the polar silane having a symmetrical electrostatic potential distribution is selected from (3-aminopropyl)triethoxysilane (KH550), (N,N-dimethyl-3-propyl)trimethoxysilane (KH556) or γ-glycidyloxypropyltrimethoxysilane (KH560).

[0017] Preferably, in the ethanol-water solution, the volume ratio of ethanol to water is 1:1-8.

[0018] Preferably, in the silane hydrolyzate, the concentration of polar silane with symmetrical electrostatic potential distribution is 25-500 mmol / L.

[0019] Preferably, in step S12, the method for preparing the film is: after coating the sulfonated cellulose material, evacuate the material for 5-30 minutes, and dry it at 75-130° C. for 0.5-5 hours; the coating method is selected from spin coating, coating or casting.

[0020] Furthermore, the method for preparing the film is: select one of the spin coating, coating or casting processes to make a sulfonated cellulose film, evacuate for 5-30 minutes in a vacuum environment of -0.5 to -0.1, and then dry at 75-130°C for 0.5-5h to obtain a 50-120μm thick SCNF film.

[0021] Preferably, the thickness of the sulfonated cellulose membrane is 50-120 μm.

[0022] Preferably, in step S13, the drying method is drying at 80-130° C. for 1-5 hours.

[0023] Furthermore, the silane hydrolyzate is prepared as follows: one of polar silanes with symmetrical electrostatic potential distribution, such as (3-aminopropyl)triethoxysilane (KH550), (N,N-dimethyl-3-propyl)trimethoxysilane (KH556), γ-glycidyloxypropyltrimethoxysilane (KH560), etc. is selected, silane (25-500mmol / L) is hydrolyzed in an ethanol / water (V:V=1:1-8) solution, and stirred at 40-80°C for 6-18 hours to obtain a silane hydrolyzate.

[0024] The present invention also provides a cellulose-based triboelectric material with high output and high stability at high temperature, which is prepared by the above preparation method.

[0025] Preferably, the high-temperature stable high-output cellulose-based triboelectric material contains a silane layer, and the thickness of the silane layer is 5-20 μm.

[0026] The present invention also provides a friction nanogenerator, wherein the positive electrode material of the friction nanogenerator is selected from the cellulose-based triboelectric material with stable high output at high temperature as described in claim 8 or 9, and the negative electrode triboelectric material is selected from perfluoroethylene propylene copolymer (FEP) film.

[0027] The friction nanogenerator based on SCNF-NH2 film is suitable for many fields such as stable high output in high temperature environment, monitoring human health as a self-powered power source, and the development of flexible sensors in extreme environments.

[0028] The technical solution of the present invention has the following advantages over the prior art:

[0029] (1) The present invention endows the cellulose nanofiber membrane with triboelectric positive properties, making it a strong triboelectric positive electrode material that can replace animal hair, polyimide and nylon. After being assembled with FEP, the charge density is as high as 140μC / m 2 . And it maintains excellent stability in an environment of 250°C.

[0030] (2) After modification, the charge dissipation rate is reduced by 83%, and the modified cellulose triboelectric material maintains excellent mechanical properties under high temperature environment.

[0031] (3) The process flow designed by the present invention is short, the equipment is simple, and the cost is low. It can significantly improve the electrical output performance and maintain stability in a high temperature environment. It has wide applications in energy collection in extreme environments, human health monitoring, flexible electronic products, and intelligent sensing. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The Fourier transform infrared spectroscopy FTIR characterization comparison diagram (a) and the energy dispersive spectrometer EDS characterization diagram (b) of the SCNF-NH2 membrane material prepared in Example 1, the SCNF material and the CNF material.

[0033] Figure 2 The deep trap density diagram (a) of the SCNF-NH2 film material, SCNF material and CNF material prepared in Example 1, the surface potential stability test diagram (b) and the output charge density diagram of SCNF-NH2 at different temperatures (c). DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0035] Example 1

[0036] (1) Preparation of SCNF-NH2 membrane

[0037] 0.8g of cellulose nanofibers with a diameter of 10nm and a length of 15μm were selected. SV was added to a mixed solution of 2mL ultrapure water and 90mL isopropanol, with a ratio of SV to cellulose of 20%, and ultrasonic dispersion was performed for 1 hour. Then NaOH was added to the above solution, with a weight ratio of NaOH to SV of 8%, and stirred for 2 hours, then heated to 70℃ and stirred for 12 hours. The spin coating process was selected, and the Jiang Shangru solution was made into a SCNF film, which was vacuumed for 10min under a vacuum environment of -0.2, and then dried at 80℃ for 4h to obtain a 70μm thick SCNF film. KH550 was selected, and KH550 (60mmol / L) was hydrolyzed in an ethanol / water (V:V=1:3) solution, and stirred at 60℃ for 8 hours to obtain a silane hydrolyzate. The silane hydrolyzate was also applied to the SCNF surface by spot coating. Dry at 100℃ for 2 hours, and the thickness of the silane layer after drying is 15μm to make SCNF-NH2.

[0038] (2) Preparation of triboelectric nanogenerator

[0039] The modified SCNF-NH2 film prepared above was selected as the positive electrode of the triboelectric nanogenerator and the FEP film negative electrode with a size of 4πcm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 8N and a frequency of 3Hz.

[0040] (3) The open circuit voltage of the positive electrode of the triboelectric nanogenerator using pure cellulose nanofiber membrane without any modified materials is 60V; the open circuit voltage of the triboelectric nanogenerator using the SCNF-NH2 membrane based on this embodiment is 150V. The deep trap density is increased by an order of magnitude, and the charge dissipation rate is reduced by 80%. Due to the presence of multiple non-covalent bonds in cellulose, the cellulose-based triboelectric material maintains 95% of the charge density at 250°C and exhibits excellent mechanical properties. A 22μF capacitor is quickly charged to 9V within 7s, which can charge 200 LED lights.

[0041] Example 2

[0042] (1) Preparation of SCNF-NH2 membrane

[0043] 1.0g of cellulose nanofibers with a diameter of 10nm and a length of 18μm were selected. SV was added to a mixed solution of 2mL ultrapure water and 100mL isopropanol, with a ratio of SV to cellulose of 22%, and ultrasonic dispersion was performed for 1 hour. Then NaOH was added to the above solution, with a weight ratio of NaOH to SV of 10%, and stirred for 2 hours, then heated to 80℃ and stirred for 15 hours. The above solution was made into a SCNF film by spin coating, and vacuumed for 15min under a vacuum environment of -0.1, and then dried at 90℃ for 2h to obtain a 60μm thick SCNF film. KH550 was selected, KH556 (60mmol / L) was hydrolyzed in an ethanol / water (V:V=1:2) solution, and stirred at 70℃ for 9 hours to obtain a silane hydrolyzate. The silane hydrolyzate was also applied to the surface of the SCNF film by spot coating. Dry at 110℃ for 2 hours, and the thickness of the silane layer after drying is 13μm, to obtain a SCNF-NH2 film.

[0044] (2) Preparation of triboelectric nanogenerator

[0045] The SCNF-NH2 film prepared above was selected as the positive electrode of the triboelectric nanogenerator and the FEP film negative electrode with a size of 4πcm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 8N and a frequency of 3Hz.

[0046] (3) The open circuit voltage of the positive electrode of the triboelectric nanogenerator using pure cellulose nanofiber membrane without any modified materials is 60V; the open circuit voltage of the triboelectric nanogenerator using the SCNF-NH2 membrane based on this embodiment is 145V. The deep trap density is increased by one order of magnitude, and the charge dissipation rate is reduced by 78%. Due to the presence of multiple non-covalent bonds in cellulose, the cellulose-based triboelectric material maintains a charge density of 93% at a high temperature of 250°C and exhibits excellent mechanical properties. A 22μF capacitor is quickly charged to 9V in 8.5s, which can charge 190 LED lights.

[0047] Example 3

[0048] (1) Preparation of SCNF-NH2 membrane

[0049] 1.2g of cellulose nanofibers with a diameter of 8nm and a length of 15μm were selected. SV was added to a mixed solution of 2mL ultrapure water and 80mL isopropanol, with a ratio of SV to cellulose of 25%, and ultrasonic dispersion was performed for 1 hour. Then NaOH was added to the above solution, with a weight ratio of NaOH to SV of 10%, and stirred for 2 hours, then heated to 80℃ and stirred for 10 hours. The spin coating process was selected, and the Jiang Shangru solution was made into a SCNF film, which was vacuumed for 10min under a vacuum environment of -0.1, and then dried at 100℃ for 2h to obtain a 80μm thick SCNF film. KH556 was selected, KH550 (40mmol / L) was hydrolyzed in an ethanol / water (V:V=1:1-8) solution, and the silane hydrolyzate was obtained by stirring at 70℃ for 8 hours. The silane hydrolyzate was also applied to the surface of the SCNF by spot coating. Dry at 120℃ for 2 hours, and the thickness of the silane layer after drying is 12μm, to obtain SCNF-NH2.

[0050] (2) Preparation of triboelectric nanogenerator

[0051] The SCNF-NH2 film prepared above was selected as the positive electrode of the triboelectric nanogenerator and the FEP film negative electrode with a size of 4πcm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 8N and a frequency of 3Hz.

[0052] (3) The open circuit voltage of the positive electrode of the triboelectric nanogenerator using pure cellulose nanofiber membrane without any modified materials is 60V; the open circuit voltage of the triboelectric nanogenerator using the SCNF-NH2 membrane based on this embodiment is 160V. The deep trap density is increased by one order of magnitude, and the charge dissipation rate is reduced by 82%. Due to the presence of multiple non-covalent bonds in cellulose, the cellulose-based triboelectric material maintains a charge density of 97% at a high temperature of 250°C and exhibits excellent mechanical properties. A 22μF capacitor is quickly charged to 9.3V within 7s, which can charge 210 LED lights.

[0053] Effect evaluation 1

[0054] Compared with SCNF, the FT-IR spectra of SCNF and SCNF-NH2 showed a decrease at 1175 and 1210 cm -1 The absorption peaks corresponding to O=S=O and SO were shown at the positions, respectively, which indicated that the sulfonic acid groups were successfully introduced into SCNF. Figure 1 In addition, the 1578 and 780 cm -1 The characteristic absorption peaks corresponding to -NH2 and -Si-OC- indicate that APTES was successfully grafted onto the surface of SCNF ( Figure 1In addition, the sulfur element associated with the sulfonic acid group and the silicon element associated with APTES were detected by EDS analysis ( Figure 1 b).

[0055] The isothermal surface potential decay model was used to analyze the energy distribution of carrier traps, and the surface trap state distribution of the material was explored. It was found that compared with CNF, the deep trap density of SCNF-NH2 was significantly improved ( Figure 2 a). Moreover, the material was corona treated and the surface potential was observed. It was found that the surface potential decay of SCNF-NH2 was significantly slowed down over time ( Figure 2 b). This will capture charge efficiently, suppressing charge dissipation and thermal radiation effects in high temperature environments. Output initially increases slightly, reaching 152μC / m at 200°C 2 The peak value ( Figure 2 c). This may be because high temperature accelerates the volatilization of water molecules that inhibit charge transfer, increases the electron energy level, increases the possibility of high-energy electrons escaping from the trap, and generates more transferred electrons. However, since the deep trap density on the surface of SCNF-NH2 is significantly higher, the high energy required for carrier escape also increases, thereby improving the high-temperature stability of the material output.

[0056] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a cellulose-based triboelectric material with stable high output at high temperature, characterized in that: The steps include: S11: mixing a nanocellulose material, water, isopropanol and sodium vinyl sulfonate, adding alkali and reacting at 40-95° C. for 5-40 hours to obtain a sulfonated cellulose material; the nanocellulose material is selected from cellulose nanofibers, quaternized cellulose nanofibers, carboxylated cellulose nanofibers or bacterial cellulose; S12: preparing the sulfonated cellulose material into a membrane to obtain a sulfonated cellulose membrane; S13: Coating silane hydrolyzate on the surface of the sulfonated cellulose membrane and drying it to obtain the cellulose-based triboelectric material that is stable and has high output at high temperatures; the silane hydrolyzate is obtained by mixing polar silane with symmetrical electrostatic potential distribution in an ethanol aqueous solution at 40-80°C for 6-18h; the coating method is selected from spin coating, spot coating or coating.

2. The preparation method according to claim 1, characterized in that In the step S11, the diameter of the nanocellulose material is 3-20 nm and the length is 1-20 μm.

3. The preparation method according to claim 1, characterized in that: In the step S11, the mass ratio of sodium vinyl sulfonate to the nanocellulose material is 8-72:100, and the mass ratio of the alkali to the sodium vinyl sulfonate is 6-16:

100.

4. The preparation method according to claim 1, characterized in that: The polar silane with symmetrical electrostatic potential distribution is selected from (3-aminopropyl)triethoxysilane, (N,N-dimethyl-3-propyl)trimethoxysilane or γ-glycidyloxypropyltrimethoxysilane.

5. The preparation method according to claim 1, characterized in that: In the step S12, the method for preparing the film is: after coating the sulfonated cellulose material, evacuate for 5-30 minutes, and dry at 75-130° C. for 0.5-5 hours; the coating method is selected from spin coating, coating or casting.

6. The preparation method according to claim 1, characterized in that: The thickness of the sulfonated cellulose membrane is 50-120 μm.

7. The preparation method according to claim 1, characterized in that: In step S13, the drying method is drying at 80-130° C. for 1-5 hours.

8. A cellulose-based triboelectric material with high output and high stability at high temperature prepared by the preparation method according to any one of claims 1 to 7.

9. The high-temperature stable high-output cellulose-based triboelectric material according to claim 8, characterized in that: The high-temperature stable high-output cellulose-based triboelectric material contains a silane layer, and the thickness of the silane layer is 5-20 μm.

10. A friction nanogenerator, characterized in that: The positive electrode material of the friction nanogenerator is selected from the cellulose-based triboelectric material with stable high output at high temperature as described in claim 8 or 9, and the negative electrode triboelectric material is selected from perfluoroethylene propylene copolymer film.

Citation Information

Patent Citations

  • Modified cellulose nanofibril-based flexible friction nano-generator

    CN111082698A

  • Composite full-flexible power generation unit body and human body wearable electronic device

    CN111554793A

  • Flexible Archimedes spiral friction nanometer generator and application thereof in intelligent insole

    CN117040310A

  • Triboelectricity specialty paper and application thereof

    CN117230661A

  • A composition for fuel cell membranes and a process for the preparation thereof

    US20220311037A1